Tracing clinically-relevant antimicrobial resistances in Acinetobacter baumannii-calcoaceticus complex across diverse environments: a study spanning clinical, livestock, and wastewater treatment settings - Savin, Mykhailo; Sib, Esther; Heinemann, Celine; Eichel, Vanessa; Nurjadi, Dennis; Klose, Marian; Andre Hammerl, Jens; Binsker, Ulrike; Mutters, Nico T. (Environment international, 2024)
Acinetobacter baumannii has become a prominent nosocomial pathogen, primarily owing to its remarkable ability to rapidly acquire resistance to a wide range of antimicrobial agents and its ability to persist in diverse environments. However, there is a lack of data on the molecular epidemiology and its potential implications for public health of A. baumannii strains exhibiting clinically significant resistances that originate from non-clinical environments. Therefore, the genetic characteristics and resistance mechanisms of 80 A. baumannii-calcoaceticus (ABC) complex isolates, sourced from environments associated with poultry and pig production, municipal wastewater treatment plants (WWTPs), and clinical settings, were investigated. In total, our study classified 54 isolates into 29 previously described sequence types (STs), while 26 isolates exhibited as-yet-unassigned STs. We identified a broad range of A. baumannii STs originating from poultry and pig production environments (e.g., ST10, ST238, ST240, ST267, ST345, ST370, ST372, ST1112 according to Pasteur scheme). These STs have also been documented in clinical settings worldwide, highlighting their clinical significance. These findings also raise concerns about the potential zoonotic transmission of certain STs associated with livestock environments. Furthermore, we observed that clinical isolates exhibited the highest diversity of antimicrobial resistance genes (ARGs). In contrast to non-clinical isolates, clinical isolates typically carried a significantly higher number of ARGs, ranging from 10 to 15. They were also the exclusive carriers of biocide resistance genes and acquired carbapenemases (blaOXA-23, blaOXA-58, blaOXA-72, blaGIM-1, blaNDM-1). Additionally, we observed that clinical strains displayed an increased capacity for carrying plasmids and undergoing genetic transformation. This heightened capability could be linked to the intense selective pressures commonly found within clinical settings. Our study provides comprehensive insights into essential aspects of ABC isolates originating from livestock-associated environments and clinical settings. We explored their resistance mechanisms and potential implications for public health, providing valuable knowledge for addressing these critical issues.